The Probe Based Confocal Laser Endomicroscopy (pCLE) in Locally Advanced Gastric Cancer: A Powerful Technique for Real–Time Analysis of Vasculature - Capuano, Alessandra; Andreuzzi, Eva; Pivetta, Eliana; Doliana, Roberto; Favero, Andrea; Canzonieri, Vincenzo; Maiero, Stefania; Fornasarig, Mara; Magris, Raffaella; Cannizzaro, Renato; Mongiat, Maurizio; Spessotto, Paola (Frontiers in Oncology, 2019)
Probe based confocal laser endomicroscopy (pCLE) is an advanced technique which provides imaging of gastrointestinal mucosa at subcellular resolution and, importantly, a valid tool for the evaluation of microvasculature during endoscopic examination. In order to assess intratumoral vascularization and the efficiency of blood flow in locally advanced gastric cancer, we examined 57 patients through pCLE imaging. The vascular alterations in gastric cancer were mainly characterized by leakage and by the presence of tortuous and large size vessels. Defects in blood flow were detected very rarely. No association between the angiogenic score and the gastric tumor site or histological type was observed. Interestingly, no correlation was also found with the tumor grading indicating that the vascular angiogenic anomalies in gastric cancer represent an early pathological event to be observed and detected. The majority of patients displayed unchanged vascular alterations following neoadjuvant chemotherapy and this positively correlated with stable or progressive disease, suggesting that an unaltered angiogenic score could per se be indicative of poor therapeutic efficacy. Different vascular parameters were evaluated by immunofluorescence using bioptic samples and the vessel density did not correlate with clinical staging, site or histologic type. Interestingly, only CD105, Multimerin-2 and GLUT1 were able to discriminate normal from tumoral gastric mucosa. Taken together, these findings indicate that functional and structural angiogenic parameters characteristic of tumor blood network were fully detectable by pCLE. Moreover, the evaluation of tumor vasculature by real-time assessment may provide useful information to achieve tailored therapeutic interventions for gastric cancer patients.